Bi–Zn codoping in GeTe synergistically enhances band convergence and phonon scattering for high thermoelectric performance. Issue 41 (6th October 2020) - Guo, Zhe; Zhang, Qiang; Wang, Hongxiang; Tan, Xiaojian; Shi, Fanfan; Xiong, Chenglong; Man, Na; Hu, Haoyang; Liu, Guoqiang; Jiang, Jun
Abstract : Bi–Zn codoping promotes valence band convergence and strengthens multiple defect-phonon scattering in GeTe, leading to obviously improved thermoelectric properties. Abstract : As an attractive lead-free thermoelectric candidate, GeTe-based materials have been intensively studied in recent years. However, the ZT value of pristine GeTe is limited around unit owing to the excessive hole concentration by intrinsic Ge vacancies. In this work, we report the synergistic enhancement of thermoelectric properties in rhombohedral GeTe by Bi–Zn codoping. It is found that Bi doping can effectively optimize the carrier concentration. Density functional calculations demonstrated that both Zn doping and the reduced c / a ratio by Bi doping could promote valence band convergence and Seebeck coefficient enhancement. Furthermore, lattice thermal conductivity is also significantly suppressed due to the Bi–Zn codoping introduced phonon scattering centers including point defects, Ge nano-precipitates, herringbone domains, twin boundaries, concentrated stress and density dislocations in the matrix. Consequently, a peak ZT of 2.0 at 700 K and a ZT ave of 1.35 from 400 to 800 K are realized in Ge0.9 Bi0.06 Zn0.04 Te.